Intervensi Gaya Hidup Sehat bagi Lansia melalui Senam Hipertensi - Syamdarniati; Lalu Amri Yasir; Anna Layla Salfarina; Fitri Romadonika (Insan Kreasi Media, 2025)
This community service activity aims to improve the knowledge and skills of older adults in adopting a healthy lifestyle through regular hypertension exercise sessions in Mambalan Village, within the Penimbung Community Health Center (Puskesmas) coverage area. The methods used included health education on hypertension control, hypertension exercise training, and blood pressure monitoring before and after the session. The activity was conducted over four weeks with the active participation of 30 older adults. Data were collected through direct observation, blood pressure measurements, and brief interviews to assess changes in health behavior. The results of the activity showed an increase in elderly knowledge about the importance of a healthy lifestyle, increased participation in physical activity, and a decrease in average systolic and diastolic blood pressure after regularly participating in hypertension exercises. The elderly also reported an increased sense of fitness and enthusiasm for daily activities. In conclusion, the hypertension exercise intervention has proven effective as a form of education and promotion of a healthy lifestyle for the elderly in Mambalan Village. This program is expected to be sustainable with the support of the Penimbung Community Health Center and local health cadres as part of community-based non-communicable disease prevention effort.